PERAN DPRD DALAM IMPLEMENTASI FORMULASI PERATURAN DAERAH NOMOR 11 TAHUN 2016 - Febri Yuliani, Syahrial, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
The Role of DPRD in Implementation of Regional Regulation Formulation Number 11 Year 2016. The purpose of this study is to analyze the role of the Regional People’s Representative Council (DPRD) in the Implementation of Bengkalis Regency Medium-Term Development Plan (RPJMD) Formulation and to find out the constraints of the Regional Development Plan Regional Regulation Middle Area (RPJMD) of Bengkalis Regency in 2016- 2021. This study uses a qualitative approach. Primary data is obtained directly through interviews with key informants from Bappeda and Members of the Bengkalis District Representative Council (DPRD) for the 2014-2019 period. The results of this study indicate that in the preparation of the Regional Medium Term Development Plan (RPJMD), there are five roles of the Regional People’s Representative Council (DPRD) in the Implementation of the Bengkalis Regency Medium Term Development Plan (RPJMD) Formulation in 2016-2021, namely 1) Special Committees (Special Committee) Regional People’s Legislative Assembly (DPRD) discusses with regard to the stages of the preparation of the Regional Medium-Term Development Plan (RPJMD), 2) Seeing and paying attention to the relationship of the elected district head’s vision and mission with the proposed Regional Medium-Term Development Plan (RPJMD), 3) Exploring comprehensively and holistically between vision and mission with the regional Medium Term Development Plan (RPJMD), 4) Paying attention and discussing the indicators to be achieved in the Regional Medium Term Development Plan (RPJMD) carefully, and 5 ) The Special Committee reported the results of the discussion and conclusions at the Dew plenary meeting the Bengkalis Regional Representative (DPRD) in order to seek approval from the factions to establish a regional Medium Term Development Plan (RPJMD) into the Regional Medium-Term Development Plan (RPJMD). The obstacles that caused the delay of the Bengkalis Regency Medium-Term Development Plan (RPJMD) were stipulated, namely Political Communication which had not yet been disbursed, Local Government did not implement the Public Consultation Stages Forum, the difficulty in obtaining data for the Regional Medium-Term Development Plan (RPJMD), Regent does not directly capture existing problems and schedules that are too late to be included because the Regional People’s Legislative Assembly (DPRD) is conducting a recess.